Exposure to English: How Significance English Exposure to English Achievement - Nur Fajar; Putri, Kristanti Yuntoro; Sulistyanto, Irwan (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
The purpose of this study is to find out the exposure that is able to influence individuals’ on English achievement and to investigate the influence of English exposure on English achievement. The students are given five sets of likert scale type of questionnaire as the instrument of this study. Modification a language exposure questionnaire, the researcher indentifies the activities that exposed students to the target language. The subject of this study is 46 students of 2022 academy class from English Education Department at Kadiri Islamic University. Firstly, the result of study found that students were mostly exposed to English language through Media compared to exposure at school, which higher than their exposure at home or through their friends. It showed students acquire much of their exposure through media. Secondly, the study indicated that it was only 19.7% of the significance between English exposures on English achievement. It can be concluded that it is a low exposure on English achievement and there is no significance influence of English exposure on English achievement